Starmerella aceti f.a., sp nova, an ascomycetous yeast species isolated from fungus garden of the leafcutter ant Acromyrmex balzani - Melo, Weilan G. P. [UNESP]; Arcuri, Silvio L. [UNESP]; Rodrigues, Andre [UNESP]; Morais, Paula B.; Meirelles, Lucas A. [UNESP]; Pagnocca, Fernando C. [UNESP] (Soc General Microbiology, 2014)
A novel yeast-species was recovered from the fungus garden of the leaf-cutting ant Acromyrmex balzani (Hymenoptera: Formicidae). The growth of the novel yeast species is limited by its ability to metabolize only a few carbon and nitrogenous compounds. A remarkable characteristic of this strain is the vigorous growth in 1% acetic acid. Sequence analysis of the D1/D2 domains of the LSU rRNA gene showed that the novel species belongs to the Starmerella clade and is phenotypically and genetically divergent from currently recognized species in this clade. Described here as Starmerella aceti f.a., sp. nov., it differs by 37 nucleotide substitutions in the D1/D2 region from Starmerella jinningensis CBS 11864(T), the most closely related species. The type strain of Starmerella aceti sp. nov. is TO 125(T) (=CBMAI 1594(T)=CBS 13086(T)).